Efforts to Improve Students' Logical Thinking Skills in Islamic Education Learning by Using Illustrated Story Books: A study at SD Negeri 20 Meulaboh - Riza, Rasma; Sari, Mala (Jurnal Profesi Guru Indonesia, 2025)
This research aims to improve students' logical thinking skills in Islamic Religious Education learning at SD Negeri 20 Meulaboh through the use of picture storybook media. The research uses the Classroom Action Research (PTK) method with two implementation cycles. The research subjects consisted of 20 students in class V who participated in PAI learning. Data collection instruments are in the form of logical thinking tests, student activity observation sheets, and documentation of the learning process. The results of the study showed a significant increase in students' logical thinking skills. In the initial condition, only 40% of students showed good logical thinking skills, increasing to 65% in the first cycle, and reaching 85% in the second cycle. Student activities in learning also increase with a more interactive and participatory classroom atmosphere. The conclusion of this study states that the use of picture storybook media is effective in improving students' logical thinking skills in Islamic Religious Education learning at SD Negeri 20 Meulaboh. These findings make an important contribution to the development of creative and fun learning methods to improve students' critical and logical thinking skills.